Pengembangan Modul Pembelajaran Pemrograman Dasar Berbasis Adobe Flash CS6 Bagi Siswa Kelas XI RPL - Afif Rahman Riyanda; Wayan Suana (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2019)
This research is based on the low learning outcomes of the XI Rekayasa perangkat Lunak (RPL) students in Basic Programming Subjects. The purpose of this study develops a learning resource for a valid, practical and effective learning module on the subject of computer assembly and installation. The research method used in this research is Research and Development (RD) using ADDIE's development model which includes five stages namely (1) Analysis:, (2) Design:, and (3) Development:. (4) Implementation: (5) Evaluation. The results obtained from this research and development are as follows. (1) The product produced from this research is an Adobe flash CS6-based product for the XI-grade students of software engineering. (2) The development of this module has been through expert level of module validation, (3) The development of this module has been through the practicality of the response of the teacher with the percentage of the result is 81.40%, and the practical level of the student response with the result of the percentage is 85.81% then categorized practically. (4) The development of this module has been through the effective stage of showing the value of 86.36% of students reach Minimal submission criteria, then can be categorized effectively. Keywords: Learning modules, Adobe flash CS6, Research and Development, ADDIEDOI : http://dx.doi.org/10.23960/jpvti.v1.i2.201901